2021
DOI: 10.24083/apjhm.v16i1.597
|View full text |Cite
|
Sign up to set email alerts
|

Hong Kong’s Growing Need for Palliative Care Services and the Role of the Nursing Profession

Abstract: This viewpoint paper explores the growing emphasis and social need for palliative care from a global perspective, juxtaposed against the Hong Kong status quo and its increasing need for such services. It further highlights that the role of nursing within palliative care is central to patients receiving the best quality of care. Hong Kong’s current delivery models are generally insufficient and can be improved by the adoption of five recommended policy changes, which reinforce the position of nurses as vital to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Post-1978 China's reform and opening-up policy has precipitated a pervasive trend of labor migration from rural to urban areas, wherein the remittances from migrating offspring have enabled parents to access superior healthcare and nutritional resources (Ao et al 2016;Yip et al 2021). Nevertheless, Chang et al (2011) observed that the departure of family members significantly augments the labor burden on the older adults in rural communities, compelling them to dedicate extended periods to agricultural tasks and domestic responsibilities for themselves and their offsprings.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Post-1978 China's reform and opening-up policy has precipitated a pervasive trend of labor migration from rural to urban areas, wherein the remittances from migrating offspring have enabled parents to access superior healthcare and nutritional resources (Ao et al 2016;Yip et al 2021). Nevertheless, Chang et al (2011) observed that the departure of family members significantly augments the labor burden on the older adults in rural communities, compelling them to dedicate extended periods to agricultural tasks and domestic responsibilities for themselves and their offsprings.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Family members require access to comprehensive information to make informed decisions about hospice enrollment (Tate et al, 2020). Professional hospice care training and collaboration among healthcare professionals are crucial for accomplishing such requirements, as Yip et al (2021) emphasized.…”
Section: Influence Of Tour On the Willingnessmentioning
confidence: 99%
“…Implementation leadership competencies refer to the leadership knowledge, skills and abilities required to influence staff to implement EBP [ 20 , 21 ]. Leadership knowledge is the theoretical or practical understanding of leadership that’s acquired through experience or education, skills refer to the use of this knowledge in execution or performance, and ability is inherent or developed quality that enable a person to perform leadership tasks effectively [ 22 ].…”
Section: Introductionmentioning
confidence: 99%